The classification of technical devices in the training process of athletes playing games - Guba V. P.; Rodin A. V.; Skripko A. D.; Pleshakov A. A. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to examine, summarize, and categorize the technological instruments that enhance athletic performance in competitive sports.